Selected tumor markers in the routine diagnosis of endometrial and cervical cancer - Badowska-Kozakiewicz, Anna (Menopause Review/Przegląd Menopauzalny, 2012)
Endometrial cancer occurs mostly in postmenopausal women with the peak incidence at the age of 55-65. An increasing number of young women in the reproductive age catching the disease is also observed. In terms of the incidence of cancer in women, endometrial cancer in Poland ranks sixth. Cervical carcinoma is the most frequent disease of the reproductive organ and is the second most common cancer in women. In Poland, cervical carcinoma accounts for about 7.7% of all malignancies in women. The most common deaths occur in the age groups of 45-49 and 65-74 years. Both endometrial cancer and cervical carcinoma have a high mortality, and therefore new methods of diagnosis and new tumor markers that enable earlier diagnosis of cancer are searched. Tumor markers are substances that can be detected in higher than normal amounts in the blood, urine, or body tissues of some patients with certain types of cancer. Tumor markers play an important role in the diagnosis of cancer. In the routine diagnosis of endometrial and cervical cancer, a lot of markers are applied such as CA 125, squamous cell carcinoma antigen (SCC-Ag), tissue polypeptide antigen (TPA), tissue polypeptide specific antigen (TPS) and CYFRA 21-1, and vascular growth factor (VEGF), granulocyte colony stimulating factor (G-SCF) and macrophage colony stimulating factor (M-SCF). However, new chemical compounds useful in early diagnosis, monitoring treatment and detecting recurrence of endometrial cancer and cervical carcinoma are constantly looked for.